2020
DOI: 10.1101/2020.05.15.098228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidimensional trophic niche revealed by complementary approaches: gut content, digestive enzymes, fatty acids and stable isotopes in soil fauna

Abstract: 15 1. The trophic niche of an organism is tightly related to its role in the ecosystem and can 16(2) described variation of these parameters in collembolan species, families and life 31 forms. 32 3. Correlation between trophic niche parameters of different methods was weak or absent in 33 45 out of 64 pairwise comparisons, reflecting that only some parameters provide similar 34 information. Gut content and fatty acids provided comparable information on fungivory 35 and plant feeding in Collembola. By contrast,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The trophic resources used by soil microarthropods can be determined in a complementary way by using different methods (Potapov et al 2020;Walter, Kaplan, and Permar 1991) We found that a large proportion of the resources are defined as taxonomic categories of species, genera, and families, which would be important to estimate the diets of higher taxonomic groups. The available information for low taxonomic levels could be used as a reference to address the problem of what the use of soil resources will be like by higher level taxonomic groups (Bedano 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trophic resources used by soil microarthropods can be determined in a complementary way by using different methods (Potapov et al 2020;Walter, Kaplan, and Permar 1991) We found that a large proportion of the resources are defined as taxonomic categories of species, genera, and families, which would be important to estimate the diets of higher taxonomic groups. The available information for low taxonomic levels could be used as a reference to address the problem of what the use of soil resources will be like by higher level taxonomic groups (Bedano 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Estimating the diet of organisms provides the foundation for understanding trophic interactions by characterizing how trophic resources are used by consumers within the soil ecosystem. Furthermore, it provides much-needed information on their trophic niches, their nutritional physiology, and the flows of matter and energy throughout the soil ecosystem (JM Nielsen et al 2018; Potapov et al 2020). The empirical characterization of trophic interactions is challenging due to the spatial and temporal complexity of feeding patterns, and the limitations of the methods to identify and quantify the components of the diet (JM Nielsen et al 2018; Pankhurst, Doube, and Gupta 1997; Walter, Kaplan, and Permar 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data (Tables S1 –S4) supporting the results of the study are available from the Dryad Digital Repository https://doi.org/10.5061/dryad.gtht76hm6 (Potapov et al., 2021 ).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Whenever taking new measurements, we could, for example, make use of gut content analysis, digestive enzymes, fatty acids, and stable-isotope analysis or combine several of these analyses to identify a multidimensional trophic niche (Potapov et al, 2020).…”
Section: Food-web Topologymentioning
confidence: 99%